Bronchial carcinoid tumour: a report of three cases - H. Ziyadi; B. Daher; S. Afandi; N. Yassine (International Journal of Scientific Research and Innovative Studies, 2026)
Bronchial carcinoid tumours are rare neuroendocrine tumours, accounting for 1–2% of all lung cancers worldwide. Despite their low incidence, their diagnosis remains a clinical challenge due to their often-misleading presentation. We report three cases managed in the Respiratory Medicine Department at Sheikh Khalifa International University Hospital, involving two men and one woman, with a mean age of 52 years. Clinical manifestations were varied, ranging from haemoptysis and chronic cough to incidental discovery, illustrating the symptomatic diversity of this condition. The diagnosis, suspected on imaging and bronchoscopy, was confirmed by histological and immunohistochemical examination. Management involved complete surgical resection in all patients, with a favourable outcome without the need for adjuvant therapy. These results confirm that carcinoid tumours, although rare, have an excellent prognosis when surgery is performed early, with a 5-year survival rate often exceeding 90%. Conclusion: it is essential to consider this diagnosis in the presence of any persistent bronchial symptoms in order to ensure optimal management. Keywords: Bronchial carcinoid tumour – Neuroendocrine tumour – Haemoptysis – Thoracic surgery – Prognosis. Received Date: February 22, 2026 Accepted Date: March 14, 2026 Published Date: April 02, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/717